2010
DOI: 10.3109/14653240903350265
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of stress urinary incontinence with adipose tissue-derived stem cells

Abstract: Background-Effective treatment for stress urinary incontinence (SUI) is lacking. This study investigates whether transplantation of adipose tissue-derived stem cells (ADSCs) can treat SUI in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 33 publications
2
171
1
3
Order By: Relevance
“…In 2010, we found that transplantation of ADSCs via urethral or intravenous injection was effective in the treatment or prevention of SUI in a vaginal balloon dilation model [73]. Activation of VEGF and ERK1/2 signaling pathway might be responsible for the paracrine effects of ADSCs in this model [74].…”
Section: Stress Urinary Incontinence (Sui)mentioning
confidence: 99%
“…In 2010, we found that transplantation of ADSCs via urethral or intravenous injection was effective in the treatment or prevention of SUI in a vaginal balloon dilation model [73]. Activation of VEGF and ERK1/2 signaling pathway might be responsible for the paracrine effects of ADSCs in this model [74].…”
Section: Stress Urinary Incontinence (Sui)mentioning
confidence: 99%
“…To date, treatment avenues for voiding dysfunction and urinary incontinence have focused on this potential to restore function via differentiation to replace injured or diseased tissues such as smooth or striated muscle for urethral sphincter regeneration and urothelial tissue for bladder, urethral, and upper urinary tract reconstruction [Al-Awqati and Oliver, 2002;Chermansky et al 2004b;Cruz et al 2011]. It is thought that MSCs restore function in SUI primarily by their ability to differentiate into multiple cell lineages, with animal studies demonstrating increases in urethral muscle, nerves, and connective tissue following MSC injection [Chermansky et al 2004b;Fu et al 2010;Kim et al 2010;Lin et al 2010]. MSCs have also been induced to differentiate into a smooth muscle phenotype when exposed to conditioned media from smooth muscle cell cultures or when induced with specific myogenic growth factors for application to bladder reconstruction .…”
Section: Stem Cell Differentiationmentioning
confidence: 99%
“…Stem cells may also exert a therapeutic effect via the secretion of bioactive factors that have antiapoptotic, antiscarring, neovascularization, and immunomodulatory effects on innate tissues and can direct innate stem and progenitor cells to the area of injury [Gnecchi et al 2008]. Multiple treatment avenues using stem cells for voiding dysfunction, especially SUI, have been evaluated with preclinical animal models and clinical trials demonstrating their potential to restore function via direct effects on the underlying mechanisms that lead to incontinence or voiding dysfunction [Chermansky et al 2004a;Carr et al 2008;Fu et al 2010;Huang et al 2010;Kim et al 2010;Lim et al 2010;Lin et al 2010;Cruz et al 2011;Woo et al 2011;Lee et al 2012;Carr et al 2013;Dissaranan et al 2013;Gotoh et al 2013;Rovner, 2013]. Nonetheless, many challenges remain to translate these promising results to clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant for patients with bladder malignancies who require bladder augmentation or replacement but do not have enough normal, non-malignant bladder cells to use in tissue engineering applications. Other MSC such as skeletal muscle-derived progenitor cells 79-88 89-92 and adipose stem cells 80,90,91,[93][94][95][96][97][98] have been investigated as potential candidates for cell-based tissue engineering and injection therapy stress urinary incontinence (SUI), and these studies are further described in Section 5.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%